Ensinagem e aprendizagem em incubadora tecnológica: um estudo de caso na Incubadora Tecnológica de Caxias do Sul - Beltrame, Antor (My University, 2014)
This research is structured on three relevant phenomena in the contemporary economy, entrepreneurship, innovation and university-industry relationships, converging elements in the environment of technology-based business incubators. Considering that the justify to the creation of this type of incubator is the endorsement to its own context, the problem which guided the research questions was the effectiveness of the Technology Incubator of Caxias do Sul (ITEC) in the promotion of these three factors of economical development. ITEC was selected due to its relationship with the University of Caxias do Sul (UCS), one of its supporting entities, and also due to the fact that it is a unique initiative in the northeastern region of Rio Grande do Sul, one of the economically most important regions of the state. The methodology applied in the research was the case study, based on the bibliographic and documental investigation, making use of semi-structured interviews as main sources of information. Besides the incubator s management staff, representatives of all companies currently incubated, and representatives of approximately 80% of the graduated companies in activity were interviewed. The study sought to delineate the context related to entrepreneurship, innovation and university-industry relationships, which insert ITEC and, at the same time, it sought to describe the performance of ITEC in the promotion of these elements. For this, it was made use of the teaching-learning perspective respectively, while the development conditions offered by the incubator to the companies and the management practices adopted by them. The results suggest that, particularly in the recent past, the incubator has become an important mechanism for the endorsement of the mentioned context, and at the same time, it indicates the existence of a great potential to be explored, mainly in terms of innovation and university-industry relationships.
Esta pesquisa estruturou-se a partir de três relevantes fenômenos da economia contemporânea: empreendedorismo, inovação e relações universidade-empresa, elementos convergentes no ambiente das incubadoras de empresas de base tecnológica. Considerando que a justificativa para a criação deste tipo de incubadora é o fomento ao seu próprio contexto, o problema que norteou a pesquisa questionou a efetividade da Incubadora Tecnológica de Caxias do Sul (ITEC) em seu cenário. A ITEC foi selecionada por sua relação com a Universidade de Caxias do Sul (UCS), uma de suas entidades mantenedoras, bem como por se tratar de uma iniciativa única na região Nordeste, uma das regiões economicamente mais importantes do estado do Rio Grande do Sul. A metodologia utilizada na pesquisa foi o estudo de caso que, tendo por base a pesquisa bibliográfica e documental, valeu-se de entrevistas semiestruturadas como principais fontes de dados. Foram entrevistados, além da gerência da incubadora, representantes de todas as empresas incubadas e de aproximadamente 80% das empresas graduadas em atividade. O estudo procurou delinear o contexto relativo ao empreendedorismo, à inovação e às relações universidade-empresa, no qual se insere a ITEC e paralelamente, procurou-se descrever o desempenho da ITEC na promoção destes elementos. Para tanto, aplicou-se uma perspectiva baseada na ensinagem e na aprendizagem, respectivamente, enquanto condições de desenvolvimento proporcionadas pela incubadora às empresas e às práticas gerenciais adotadas por estas. Os resultados sugerem que, notadamente no passado recente, a incubadora vem se constituindo como importante mecanismo de fomento ao contexto assinalado e paralelamente indica a existência de um amplo potencial a ser explorado, especialmente em termos de inovação e relações universidade-empresa.
Keywords: Administração de empresas; Empreendedorismo; Inovação; Relações Universidade-Empresa; Incubadoras de empresas de base tecnológica; Ensinagem; Aprendizagem; Entrepreneurship; Innovation; University-industry relationships; Technology-based business incubators; Teaching-learning